PERAN GURU PPKN DALAM PENERAPAN KARAKTER SOPAN SANTUN PADA SISWA DI MTs DDI OGOAMAS - Meli Meli; Erni Nurdin (Sekolah Tinggi Keguruan dan Ilmu Pendidikan (STKIP) Dampal Selatan, 2024)
This study aims to describe the role of Civic Education teachers in implementing polite character among students at MTs DDI Ogoamas, identify the challenges faced by teachers, and examine supporting factors. The study employed a descriptive qualitative approach. It was conducted at MTs DDI Ogoamas in July–August 2024, involving a Civic Education teacher and students as research subjects. Data were collected through participatory observation, semi-structured interviews, and documentation, and were analyzed through data reduction, data display, and conclusion drawing. The findings show that the teacher’s role was implemented through habituation of polite speech and behavior, motivational guidance, direct practice of etiquette, teacher modeling, educational reprimands, and classroom rules. Character formation was also reinforced through morning routines, Qur’an reading, and congregational Dhuha prayer. The main challenges were limited monitoring of students’ behavior, low confidence among some students in displaying polite behavior, and limited cooperation between teachers and parents. Supporting factors included consistent habituation, teacher modeling, school rules, institutional support, and the surrounding environment. The study concludes that Civic Education teachers play an important role in developing polite character through consistent, humane, and continuous educational practices.